Ecotourism to sustain scenic beauty of Pulau Langkawi, Malaysia - Othman, Jamilah; Ahmad Kamaruddin, NurEmira (2016)
Ecotourism practices might be one of the important tools to sustain the natural heritage of an island environment. It has potential to flourish the tourism industry as well as providing revenue to a country. Besides that, the naturalness of the island landscapes can be continuously experienced and conserved. Perhaps, more island ecotourism developments should be promoted considering these importance. The establishment of relevant environmental policies and acts are also essential in supporting the maintenance and protection of natural resources with scenic value. Preliminary review of 26 journal articles explores the potential of adopting the ecotourism principles. So far, it is found that more theoretical studies are conducted on the issues. Thus, this paper suggests that more pragmatic studies should be collaborated between the local authorities and academics. The focused would be sustaining the scenic beauty of sensitive environments such as Pulau Langkawi.